CRUSHED TO DEATH: HEALTH AND SAFETY RIGHTS OF STONE CRUSHERS IN NORTH BENGAL, INDIA - Swapnil Chaudhuri (PEOPLE: International Journal of Social Sciences, 2025)
Silicosis, among the stone crushing laborers, is considered one of the most common fatal occupational health hazards. Various forms of crushed stone play an extremely important role in urbanization. However, a lack of awareness and the degraded working environment often deny the basic right to health and safe working conditions for stone crushers, the backbone of development worldwide. Masonry workers develop this incurable and irreparable disease due to constant inhalation of crystalline silica particles, which are commonly found in most natural and engineered stones worldwide. Over 200 migrant stone crushers in the Balason riverbed in North Bengal, India, were interviewed in 3 years to understand their socio-economic background and health impact caused by the stone crushing job. It was observed that there are usually two types of crushing methods involved to produce the required sizes of stone chips as per the industry demand: manual stone crushing and stone crushing using jaw crushers and other industrial machines. Both sites were visited to compare dust emission conditions. In the industrial site, it was hard to breathe, owing to the massive dust emissions. On the other hand, manual stone crushers were facing the typical risks of getting hurt or blinded by the stone chips. Though there are several International and Indian Laws that advocate, promote, and protect workers’ safety, it was commonly seen that the workers were working on this site without wearing any Personal Protective Equipment. This field-based qualitative study tends to analyze and highlight such an important topic, which is not only common among the stone crushers, but also prevalent among the miners, construction workers, brick, tile industry, and sandblasting industry worldwide. The goal of this research is to spread awareness worldwide through this case study and create safe working conditions for the workers.